RELATIONSHIP BETWEEN DAILY PHYSICAL ACTIVITY AND QUALITY OF SLEEP IN MAINTENANCE HEMODIALYSIS PATIENTS - Trbojević-Stanković, Jasna; Stanimirović, Sanja; Ristanović, Ljubica; Nešić, Dejan (Medical Research, 2024)
Introduction/Aim: Hemodialysis patients are often sedentary and experience high prevalence of sleep disorders. In this study we aimed to assess the level of physical activity and quality of sleep among patients on maintenance hemodialysis, and assess the relationship between these issues. Material and Methods: Seventy-one hemodialysis patients filled in the International Physical Activity Questionnaire (IPAQ) and the Pittsburgh Sleep Quality Index (PSQI) to assess their level of physical activity and their quality of sleep respectively. Basic demographic, clinical and treatment-related characteristics were obtained from electronic medicala data system, as well as results of standard laboratory analyses. Results were analyzed with Student t-test, Pearson chi-square test, linear by linear association and Spearman correlation. Results: Nearly half of the patients (46.5%) were poor sleepers with an overall PSQI 5.7 ± 4.4. Older age was significantly associated with worse sleep quality (p=0.019). Patients reported low, moderate or vigorous level of daily physical activity in 42.3%, 50.7% and 7% of cases respectively. No statistically significant associations were noted between demographic characteristics, dialysis vintage, comorbidities and level of physical activity. Distribution of good and poor sleepers was almost identical among patients with low and moderate physical activity (47% vs 53% and 50% vs 50% respectively), whereas patients with vigorous activity were mostly good sleepers (20% vs 80%), but the difference was not statistically significant (p=0.591). Conclusion: We observed no statisticaly significant association between the level of physical activity and quality of sleep in this cohort. Further research with larger sample might additionaly elucidate this issue.